Multicausal analysis of the dropout of university students from teacher training studies in Andalusia - Ibáñez-Cubillas, Pilar; López-Rodríguez, Slava; Martínez-Sánchez, Isabel; Rodríguez, José Álvarez (Frontiers in Education, 2023)
To give an answer and a solution to the inconveniences that dropout brings to universities and to society, we have studied the different approaches that exists in the actual scientific literature about the reasons of this phenomenon. The aim of this investigation is analyzing the college dropout, focalizing in students of education degrees of Andalusian universities. For doing that, we applied a standardized instrument that pretend to determine which are the factors associated to the permanence of the college students. The instrument was applied to 608 students of the first year of six Andalusian universities. Of these, 274 were studying Infant education degree and 334 Primary education degree. The study shows that a large sample of the subjects interviewed responded with higher scores 3.83, stating the need to remain in their undergraduate studies, with few references to dropping out of the university. Some of the items that have obtained the highest ratings express their desire to graduate with honors, become a good professional and practice their profession within their field of work, among others.